2018
DOI: 10.1002/ptr.6053
|View full text |Cite
|
Sign up to set email alerts
|

Luteoloside attenuates anoxia/reoxygenation‐induced cardiomyocytes injury via mitochondrial pathway mediated by 14‐3‐3η protein

Abstract: Ischemia/reperfusion (I/R) injury is the major cause of acute cardiovascular disease worldwide. 14-3-3η protein has been demonstrated to protect myocardium against I/R injury. Luteoloside (Lut), a flavonoid found in many Chinese herbs, exerts myocardial protection effects. However, the mechanism remains unclear. We hypothesize that the cardioprotective role of Lut is exerted by regulating the 14-3-3η signal pathway. To investigate our hypothesis, an in vitro I/R model was generated in H9C2 cardiomyocytes by an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…14-3-3 is the molecular target of many active ingredients of plants. We have confirmed that 14-3-3 assists PKCε, Bcl-2, and other functional proteins to locate to mitochondria and protect cardiomyocytes and vascular endothelial cells against multiple injuries [7,9,[40][41][42][43]. Further studies are needed to define specific mechanism(s) of action for Cap-activated 14-3-3η in anoxia and A/R injured cardiomyocytes.…”
Section: Discussionsupporting
confidence: 53%
“…14-3-3 is the molecular target of many active ingredients of plants. We have confirmed that 14-3-3 assists PKCε, Bcl-2, and other functional proteins to locate to mitochondria and protect cardiomyocytes and vascular endothelial cells against multiple injuries [7,9,[40][41][42][43]. Further studies are needed to define specific mechanism(s) of action for Cap-activated 14-3-3η in anoxia and A/R injured cardiomyocytes.…”
Section: Discussionsupporting
confidence: 53%
“…Propolis [96] Luteoloside [99] Eriodictyol [101] Dihydromyricetin [102] Vitexin [103] Apigenin [105] Oxidative stress…”
Section: Energy Metabolism Obstructionmentioning
confidence: 99%
“…Capsaicin [97] Quercetin [98] Luteoloside [99] Astragaloside IV [100] Eriodictyol [101] Dihydromyricetin [102] Vitexin [103] Honokiol [104] Apigenin [105] Apoptosis Capsaicin [97] Quercetin [98] Luteoloside [99] Astragaloside IV [100] Eriodictyol [101] Dihydromyricetin [102] Apigenin [105] Mitochondrial membrane potential imbalance…”
Section: Energy Metabolism Obstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galuteolin exhibited a high activity against in uenza virus (H3N2) [9]. Galuteolin could alleviate myocardial cell damage caused by myocardial ischemia-reperfusion by reducing oxidative stress response and inhibiting myocardial cell apoptosis [10]. Galuteolin blocked the activation of NF-κB and TLR2 signaling pathways, thereby reducing the in ammation, damage and apoptosis of uterine cells caused by staphylococcus aureus [11].…”
Section: Introductionmentioning
confidence: 99%